The Impact of Problem-Based Learning on Students’ Mathematical Problem-Solving Skills within the Independent Curriculum - Putri, Maifa Munsyaila (Aksioma Education Journal, 2024)
This study investigates the impact of Problem-Based Learning (PBL) on students’ mathematical problem-solving skills within the framework of the Independent Curriculum in Indonesia. The curriculum emphasizes higher-order thinking, autonomy, and contextual learning; however, national assessments show that students continue to struggle with applying mathematical concepts in authentic problem situations. To address this gap, a quasi-experimental design with a pretest–posttest non-equivalent control group was implemented involving 64 eighth-grade students. The experimental group received PBL instruction, while the control group was taught using conventional direct instruction. Data were collected using a validated Mathematical Problem-Solving Test consisting of five open-ended items and analyzed through descriptive statistics, normalized gain (N-gain), independent samples t-tests, and effect size calculations. The results revealed that the PBL group achieved significantly higher posttest scores (M = 82.14) than the control group (M = 67.45), with a high N-gain value (0.71) and a very large effect size (d = 1.84). In addition, students taught through PBL demonstrated superior performance across all problem-solving indicators, including problem understanding, planning, strategy execution, and evaluation. These findings indicate that PBL effectively promotes deeper conceptual understanding, strategic reasoning, and reflective thinking competencies central to the Independent Curriculum. This study affirms PBL as a pedagogically relevant and powerful approach for enhancing mathematical problem-solving skills in secondary education.